Ecological studies on benthic polychaetes with respect to oranic enrichment condition in Kung Krabaen, Thailand - Bamroonsak Chatananthawej (Chulalongkorn University, 2012)
Thesis (Ph.D.)--Chulalongkorn University, 2001